The Legal Regulation of the Flexible Employment Contract in the Saudi Law: An Analytical Study - Reham Ateeq Alzahrani (International Journal of Law Research and Studies, 2026)
This study examined the regulatory framework of the flexible employment contract through two main sections. The first section addressed the nature of this contract by identifying its concept and characteristics and distinguishing it from other similar contracts. The second section discussed the legal effects arising from the flexible employment contract and its termination. The study aimed to determine the adequacy of the current legal framework in regulating the flexible employment contract and organizing contractual relationships established under it. The analytical method was adopted to answer the study questions and achieve its objectives. The study concluded with several findings, most notably that the regulator has given considerable attention to this type of contract through issuing the Procedural Guide for Regulating Flexible Work and stipulating the provisions governing it in Article 27 of the Implementing Regulations of Labor Law. The study also reached several recommendations, the most significant of which is recommending that the regulator amend the definition of the flexible employment contract in order to clarify the meaning of the term “non-subordinate worker” by adopting a more precise definition that clarifies the element of subordination and the extent to which it exists within the flexible employment contract, considering that subordination is one of the most important elements distinguishing an employment contract from other types of contracts.